Spatial Planning and Tourism Development of Serifos: Towards a Framework for Sustainable Development. - Lazoglou, Miltiadis; Tziraki, Maria; Chatzinikolaou, Elissavet (Technical Annals, 2025)
This study investigates the complex interplay between tourism development and spatial planning on Serifos, a Cycladic island undergoing rapid transformation under seasonal visitor pressure. Drawing from the principles of sustainable development, the paper presents an integrated analytical approach combining geospatial diagnostics, empirical indicators, and policy evaluation. Using building footprint data and short-term rental distributions, the analysis identifies spatial stress zones, development conflicts, and regulatory gaps, especially in non-designated urban areas and protected environmental zones. The findings demonstrate that over 50% of the built surface lies outside statutory boundaries, exacerbating infrastructure strain and landscape fragmentation. A composite zoning strategy and thematic interventions are proposed, culminating in a spatial framework aligned with the island’s ecological thresholds and cultural assets. The paper concludes with legal recommendations and a proposal for establishing a permanent monitoring mechanism (DMMO) to ensure adaptive and participatory governance.